Matched - Condie, Allyson Braithwaite (Speak, 2011)
Seventeen-year-old Cassia has always trusted the Society to make the right choices for her, but when there is a "glitch" at her Matching ceremony, she is torn between marrying her best friend and a new love, which could bring disaster.